Optimization of Directional Well Trajectory - Cui Aizhen (E3S Web of Conferences)
As drilling technology and equipment continue to advance, the slot layout in China’s Bohai Sea area is becoming increasingly dense, and the design of directional well trajectories is becoming more complex, posing a high risk of collision. By applying optimization technology for directional well trajectories, including adjusting the dogleg severity, adjusting slot positions, and refining target points, the optimal trajectory design has been completed efficiently and with high quality. Taking the X8H well in the Bohai Sea as an example, verification results show that after trajectory optimization, the anti-collision situation has significantly improved. The anti-collision distance to the X3H well has increased significantly, with the minimum separation coefficient rising from 0.775 to 1.017. Similarly, the anti-collision situation with the X5H well has improved, with the separation coefficient at the minimum separation distance point increasing from 0.996 to 1.134, and the minimum value of the separation coefficient also rising from 0.852 to 0.961.